Punitiveness, stigmatization and social exclusion: reflections on the reproduction of citizen (in)security - Cano Roblero, Victor (2022)
This article aims to critically analyze the paradigm of citizen security in Costa Rica, predominant in recent decades, in light of Cornelius Castoriadis's theory of the social imaginary. Specifically, some of the symbolic and material implications that its implementation has had are shown, emphasizing how the social meanings about the subject that embodies insecurity are reflected in the implementation of public policies on citizen security, and stopping at the media dynamics that (re)produce them. Finally, it addresses how this imaginary reinforces the territorial stigmatization of people from urban-marginalized neighborhoods, and how this deepens processes of urban social exclusion, reproducing a circularity between punitiveness, stigmatization, and exclusion. Methodologically, the article draws on the review of secondary sources on the security issue in Costa Rica at the end of the 20th century and early 21st century, through which three concepts that guide the argument are defined: imaginary of (in)security, criminal subject, and territorial stigmatization. This work is expected to contribute to the reflection on comprehensive and inclusive alternatives that respect the complexity of the social and economic dynamics linked to the phenomenon of crime and citizen insecurity.